An Analysis of Inflectional Morphemes and Derivational Morphemes in Selena Gomez Talkshow About Mental Health Awareness (Gunung Djati Conference Series, 2025)
This study investigates the use of inflectional and derivational morphemes in Selena Gomez’stalkshow on mental health awareness. Using a descriptive qualitative approach, the researchanalyzes transcripts from selected episodes through purposive sampling. Data collection involvedtranscript analysis, morpheme identification, and classification based on meaning. The findingsreveal 207 total morphemes, comprising 172 inflectional morphemes (83,1%) and 35 derivationalmorphemes (16,9%). Eight types of inflectional morphemes were identified, primarily used forgrammatical functions. Derivational morphemes included noun-forming, adjective-forming, adverbforming, and verb-forming suffixes, along with verb-forming prefixes, contributing to vocabularyenrichment and meaning variation in mental health discussions.